Pulsed Light Synthesis of High Entropy Nanocatalysts with Enhanced Catalytic Activity and Prolonged Stability for Oxygen Evolution Reaction - Abdelhafiz, Ali; Tanvir, A. N. M.; Zeng, Minxiang; Wang, Baoming; Ren, Zhichu; Harutyunyan, Avetik R.; Zhang, Yanliang; Li, Ju (Advanced science, 2023)
The ability to synthesize compositionally complex nanostructures rapidly is a key to high‐throughput functional materials discovery. In addition to being time‐consuming, a majority of conventional materials synthesis processes closely follow thermodynamics equilibria, which limit the discovery of new classes of metastable phases such as high entropy oxides (HEO). Herein, a photonic flash synthesis of HEO nanoparticles at timescales of milliseconds is demonstrated. By leveraging the abrupt heating and cooling cycles induced by a high‐power‐density xenon pulsed light, mixed transition metal salt precursors undergo rapid chemical transformations. Hence, nanoparticles form within milliseconds with a strong affinity to bind to the carbon substrate. Oxygen evolution reaction (OER) activity measurements of the synthesized nanoparticles demonstrate two orders of magnitude prolonged stability at high current densities, without noticeable decay in performance, compared to commercial IrO2 catalyst. This superior catalytic activity originates from the synergistic effect of different alloying elements mixed at a high entropic state. It is found that Cr addition influences surface activity the most by promoting higher oxidation states, favoring optimal interaction with OER intermediates. The proposed high‐throughput method opens new pathways toward developing next‐generation functional materials for various electronics, sensing, and environmental applications, in addition to renewable energy conversion. Diagram showing high‐throughput synthesis of high entropy alloys/oxides (HEOs) nanoparticles, using intense pulsed light. Upon photon absorption by the substrate, temperature rises within a few milliseconds, converting mixed precursors to HEOs nanoparticles. Activity toward oxygen evolution reaction is compared to commercial IrO2 catalyst.